P-A3 Identification of proximal biomarkers of PKC agonist activity in HIV-1 latently infected cells. (January 2016) - Vemula, Sai Vikram; Maxwell, Jill; Webber, Andrea; Nefedov, Alexey; Newhard, William; Barnard, Richard; Blair, Wade; Hazuda, Daria; HMerckowell, Bonnie
Abstract : A small population of resting memory CD4+ T cells harboring transcriptionally silent, but replication competent human immunodeficiency-1 (HIV-1) proviruses is considered to be the major obstacle for HIV eradication in patients on anti-retroviral therapy (ART). Latent virus reactivation using protein kinase C (PKC) agonists is one approach the field is leveraging to flush HIV from latent reservoirs. Thus, increased understanding of the molecular mechanisms of action of this approach is necessary to inform of biological signaling as well as potential off-target effects associated with PKC agonists. We used an RNA-Seq- based approach to identify genes and pathways modulated following treatment of CD4+ T cells with PKC agonists. Primary human CD4+ T cells were treated with either PMA, Prostatin or Ingenol-3-Angelate for various time periods. At 3 and 24 hours post-treatment, cells were harvested and RNA-Seq was performed. Treatment with the three PKC agonists induced a time-dependent alteration in host cell gene expression pattern. Bioinformatic analysis revealed high similarity in the genes and pathways altered, with at least 42% of genes showing similar changes in expression between controls and the three compounds tested. Immune response pathways strongly associate with the gene expression changes observed at 3 hours post-treatment, while pathways associated with mitochondrial dysfunction and oxidative phosphorylation predominated at 24 hours. Quantitative reverse transcriptase PCR (qRT-PCR) validation of a subset of the RNA Seq data confirmed modulation of genes with higher expression levels across the 3 PKC agonists in HIV-1 latently infected Jurkat cells. Overall, our results could offer new insights into the mechanism of action of PKC agonists in latently infected cells, and therefore inform on eradication strategies for latent HIV.